Estrogen inhibits bladder overactivity in rats with cyclophosphamide‐induced cystitis via downregulating the expression of P2X3 receptors in bladder epithelium cells. Issue 1 (7th October 2021) - Liu, Xin; Yang, Yang; Gao, Ye; Zhang, Hengshuai; Zhu, Jingzhen; Dong, Xingyou; Xu, Jie
Abstract: Aims: The therapeutic effect of estrogen on interstitial cystitis/bladder pain syndrome is unclear. We aim to explore the effect of estrogen on bladder overactivity in rats with cyclophosphamide‐induced cystitis and its underlying mechanism. Methods: In vivo cystometry was used to determine the effect of estrogen on bladder excitability. The effect of estrogen on the expression of P2X3 receptors in bladder epithelium was detected by real‐time polymerase chain reaction and western blot. Effect of P2X3 receptors in bladder urothelium on stretch‐released adenosine triphosphate was performed by a Flexcell FX5000 Compression system and an Enzyme‐Linked Immunosorbent Assay Kit. Results: Estrogen deprivation significantly increased the urinary frequency, while supplementation with diarylpropionitrile (DPN), an estrogen receptor β (ERβ) agonist, alleviated the urinary frequency. 17β‐Estradiol and DPN decreased the expression of P2X3 receptors in urothelium cells which was partially inhibited by ERβ antagonist 4‐[2‐phenyl‐5, 7‐bis(trifluoromethyl)pyrazolo[1, 5‐a]pyrimidin‐3‐yl]phenol. Meanwhile, inhibiting the expression of P2X3 receptors by ERβ agonist or antagonizing the function of P2X3 receptors by selective P2X3 receptor antagonist AF‐353 or A‐317491 significantly reduced the stretch‐released ATP from urothelium cells. Conclusions: Estrogen has a direct effect on the regulation of bladder overactivity in rats with cyclophosphamide‐induced cystitis by downregulating the expression of bladder epithelial P2X3 receptors through ERβ and reducing the adenosine triphosphate released from urothelium during bladder filling, thereby inhibiting the generation of the micturition reflex.